CONTEXTUAL HERMENEUTICS OF GENDER-RELATED HADITHS: A COMPARATIVE ANALYSIS ACROSS VARIOUS ISLAMIC REGIONS - Iskandar, Amin; Arifin, Tajul (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2025)
This research is grounded in the fact that textualist interpretations of gender-related hadiths often serve to legitimize gender inequality within Muslim societies, primarily due to the absence of contextual and ethical interpretive approaches. The study aims to analyze how a contextual hermeneutic framework can deconstruct patriarchal constructions embedded in the interpretation of hadiths concerning women. Employing a descriptive-analytical approach, this research gathers data through purposive sampling of thematically gender-related hadiths, which are subsequently examined using qualitative data analysis techniques based on Norman Fairclough’s model of Critical Discourse Analysis (CDA). The findings indicate that interpretations of hadiths are strongly shaped by socio-political contexts: the Middle East generally adopts a literalist stance, South Asia exhibits ambivalence, while Southeast Asia reflects a more progressive and contextual approach. These findings imply the necessity of adopting a fiqh al-hadith methodology grounded in maqāṣid al-sharī‘ah and interpretive ethics, in order to cultivate more just and inclusive understandings of gendered hadiths.